Tuberculosis treatment outcomes and associated factors among patients treated at Bosaso TB Hospital, Bosaso, Somalia: A five-year retrospective study. - Saaid Said Jama; Mohamed Mohamud Abdi (PLoS ONE)
Introduction Tuberculosis remains a major public health problem, primarily in low- and middle-income countries. Evaluating treatment outcomes and investigating factors associated with them are essential for the treatment and control of tuberculosis. Hence, this study aims to assess the TB treatment outcomes and associated factors in Bosaso, Puntland, Somalia. Methods A 5-year facility-based retrospective study was conducted at Bosaso TB Hospital, from January 2018 to December 2022. A total of 2213 TB patients were included in this study. Demographic, clinical characteristics and treatment outcome data were gathered from the TB register using a structured checklist. Data were entered, cleaned, and analyzed using SPSS version 20. Descriptive statistics and binary logistic regression analysis were employed. A P-value of less than 0.05 was considered statistically significant. Results The overall successful treatment rate was 88.5%. The TB treatment success rate over the last three years was comparable to the global target of the End TB strategy of ≥ 90% by 2025. Patients aged 21-40 years (AOR = 0.59, 95% Cl = 0.41-0.84, p = 0.004), 41-60 years (AOR = 0.37, 95% CI = 0.25-0.55, p < 0.001), and ≥ 61 years (AOR = 0.37, 95% CI = 0.22-0.64, p < 0.001) were less likely to achieve successful treatment outcomes. Being HIV-positive (AOR = 0.41, 95% Cl = 0.21-0.79, p = 0.008) was less likely to be associated with a successful treatment outcome. Conclusion In this study, the TB treatment success rate over the last three years was comparable to the global target of the End-TB strategy of ≥ 90% by 2025. Therefore, we recommend strengthening the TB care system, conducting regular supportive supervision for TB facilities, implementing strategies to encourage drug adherence, strengthening mechanisms to minimize the anti-TB treatment default rate, improving counseling services, and giving more attention to the vulnerable age groups and HIV-positive patients.